2017
DOI: 10.1108/ribs-02-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Insurance effect on economic growth – among economies in various phases of development

Abstract: Purpose The purpose of this paper is to explore the relationship between insurance and economic growth for six (developed, emerging and developing) countries over the period of 1980 to 2015. Design/methodology/approach The study applies panel auto-regressive distributed lagged (PMG/ARDL) method to examine long-term and short-term relationship between insurance and economic growth for the USA, the UK, China, India, Malaysia and Pakistan. Findings The authors concluded that there exists a positive and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…On the other hand, [11] found a positive and significant effect of aggregate and non-life insurance activity on economic growth, while the relationship was negative for life insurance activity. A recent study by [19] in six countries which differed in terms of economic development showed a significant positive relationship between insurance penetration and per capita income. The study also found a significant positive relationship with economic growth for non-life insurance as measured by net written premiums, penetration rate and density.…”
Section: Studies Of the Relationship Between Insurance Activity And Ementioning
confidence: 93%
“…On the other hand, [11] found a positive and significant effect of aggregate and non-life insurance activity on economic growth, while the relationship was negative for life insurance activity. A recent study by [19] in six countries which differed in terms of economic development showed a significant positive relationship between insurance penetration and per capita income. The study also found a significant positive relationship with economic growth for non-life insurance as measured by net written premiums, penetration rate and density.…”
Section: Studies Of the Relationship Between Insurance Activity And Ementioning
confidence: 93%
“…Su Chi-Wei et al [11] examined the relationship between insurance development and economic growth using the bootstrap panel Granger causality test, finding two-way Granger causality between life insurance and macroeconomics in high-income countries. Rudra P. Pradhan et al [12] used Granger causality [17] and Sajid Mohy Ul Din et al [18] believed that life insurance had a positive effect on economic growth when the time selection rate and productivity of human capital were sufficiently low or for India, Pakistan There are more studies on the relationship between insurance and economic growth, but less on the relationship between the development of insurance market and economic growth, while the research on the development of foreign capital insurance market and economic growth in China is a blank.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At that in the long term, there is a negative correlation between foreign direct investment, the development of banking services and economic growth. The authors concluded that insurance is not only a service industry, it is a huge investment potential of the economy (Ul Din et al, 2017a). It is interesting to study the dynamic impact of financial institutions on economic growth based on the data from 13 European Union countries (Wu et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%